The Doctoral Journey - Bradford, Brent, (Educational Research E-Books Online, Collection 2024., 2024)
Earning a doctorate can be a daunting, yet rewarding, venture; the doctoral journey can include immeasurable sacrifice (e.g., health, family, finances). This edited volume-a collective narrative-comprises diverse educationalist perspectives from scholars who have successfully navigated the doctoral journey. Clearly articulated throughout this collective narrative, there are innumerable ways to complete the doctoral journey; the laborious journey is not a linear process but rather a lattice of ever-evolving professional and personal relationships, experiences, perspectives, and insights. Personal accounts of resilience and growth serve as sources of inspiration while offering sage advice, genuine insights, and significant analyses-all seamlessly connected. Contributors are: Laurie Hill, Makie Kortjass, Michael Paul Lukie, Ntokozo Mkhize-Mthembu, David G. Ngatia, Heather Raymond, Alessandra Romano, Pearl Subban, Kathy Toogood and Barbara van Ingen.